Anatomical Structure and Physical Properties of Newly Introduced Hevea Species - Md Allwi, Norul Izani (2006)

(untitled)
Understanding wood properties and behavior is important to evaluate the performance of producing high quality end products. A study was conducted to determine the anatomical and physical properties of new Hevea species viz Hevea pauciflora, Hevea guianensis, Hevea spruceana, Hevea benthamiana compared to the executing Hevea brasiliensis clone RRIM 912. This study was conducted in order to determine its suitability and potential usage of these woods. Five trees of 15 years old from each species were selected and felled from Rubber Research Institute of Malaysia (RRIM) Plantation at Bandar Penawar, Johor. Each tree was divided into three different portions along the height namely, bottom, middle and upper parts, and two radial samples namely outer and inner parts were chosen for comparative study on the anatomical structure and physical properties. Physical testing were conducted using ISO 3129-1975 (E) – Wood Sampling Methods and General Requirements for Physical and Mechanical Tests (Anon, 1975a). Clone RRIM 912 exhibited the longest fibre compared to other species with 1214 μm, followed by Hevea benthamiana (1200 μm), Hevea pauciflora (1189 μm), Hevea spruceana (1158 μm) and Hevea guianensis (1145 μm). Longer fibre was observed in outer wood compared to inner wood. The fibre length of these rubberwood species was increasing from bottom to the upper part of the tree. Hevea guianensis has the largest fibre diameter (24.9 μm) and lumen diameter (12.5 μm). Along the radial zones, there is no significant difference in lumen diameter either in the inner wood or in the outer wood. The cell wall thickness of Hevea pauciflora recorded the lowest with 6.08 μm, compared to the highest with 6.51 μm (Hevea spruceana). Most of these Hevea species showed decreasing pattern from outer region to inner region. Vessel diameter was found to be higher in RRIM 912 clones with 153.3 μm. The results indicated that the mean vessel diameter is larger at outer region compared to inner region. The mean vessel frequency was higher in Hevea guianensis with 2.61 per sq. mm. The increase in the amount of vessel will decrease the specific gravity and thus the strength of the wood. Wood from RRIM 912 clones showed the highest proportion of rays with 33.3%, compared to the lowest with 29.8% (Hevea spruceana). Hevea spruceana had the highest initial moisture content compared to other species. Basically, bottom part possessed the highest moisture content followed by middle and upper part, respectively. The highest specific gravity was obtained from RRIM 912 clones with 0.60, while the lowest was 0.57 (Hevea guianensis). Generally, species with a high specific gravity have corresponding high strength value. The strength properties of timber increase with decreasing moisture content. Hevea guianensis exhibited the highest percentage of shrinkages for all directions (tangential, radial and longitudinal). Overall, from the results it showed that the tangential shrinkage recorded the greatest value followed by radial shrinkage and longitudinal shrinkage. Overall, the properties of clone RRIM 912 was found to be comparatively better because of higher strength due to longer fibre length, thicker cell walls and higher specific gravity than other Hevea species. Therefore, this species can be inferred as a potential general utility timber.